Electron linac production of Co-57 for gamma-chamber calibration - Dikiy, N.P.; Dovbnya, N.A.; Repikhov, O.A.; Shlyakhov, I.N.; Uvarov, V.L.; Kravchenko, Ja.N. (Вопросы атомной науки и техники, 2001)
Gamma-chambers are widely used in medicine diagnostics to obtain an organ image investigated by means of the scintigraphy method. A radionuclide Tc-99m which is accumulated in the organ and irradiates photons with the energy Eγ=140 keV is a carrier of the information. Ukraine manufactures gamma-chambers of own elaboration. A γ-source with a photon energy of Tc-99m but with a larger half-life time is need for their plant calibration. The Co-57 sources (Eγ=122 keV, T1/2=270 days) are the most eligible for this purpose. Their traditional technology is based mainly on the reactor method and is accompanied by the large amount of the radioactive waste. The sources, obtained in such a way, can not be regenerated after their decay. The R&D Complex “Accelerator” of the NSC KIPT developed a new technology and manufactured the model – experimental batch of three Co-57 sources using bremsstrahlung of the high-current electron linac. The Co-57 generation processes in the Ni-58 target were previously investigated by means of computer simulation. The optimum accelerator operation regime and a target geometry were thus determined. The obtained sources characteristics confirmed the computer analysis data. Each of them is the plate of 28x28x1.5 mm and has the activity up to 2 mCi. The spectrum of the source measured with the Ge(Li) detector satisfies all demands. The technology developed provides a production of sufficient amount of Co-57 sources practically without any waste, as well as, a possibility of their regeneration.